PENGARUH PENERAPANPEMBELAJARAN CTL DENGAN MEDIAPREZIDESKTOP TERHADAP HASIL BELAJAR SISWA SMAN 4 PEKANBARU - Areskon Areskon; Elvi Yenti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
AbstractThe aim of this research was to know the influence of applying Contextual Teaching And Learning model by using Prezi Desktop mediatoward the students’ outcome on colloid learning. This research was experimental research by using pretest-posttest control group design and. The technique of collecting data was using test, observation, and documentation. The sample of this research was using random sampling. 32 students of 11th-grade science 5 serve as an experimental class. They were given the treatment of Contextual Teaching And Learning by using Prezi Desktop media, while 33 students of the 11th-grade science class 4 serve as a control classthat was given the conventional technique. The research found the final data used t pooled variance,so it was foundtquantification = 2,11and ttabel= 2,00 on the significant part and showed that tquantification>ttable. Thus, Ho was rejected and Ha was accepted. The coefficient category is 6.60%. So it can be concluded that Contextual Teaching and Learningmodelby using Prezi Desktop mediacan give a positive effect on the students outcome of chemical achievement especially on colloid learning of 11th-grade science class at State Senior High School 4 Pekanbaru.Keywords: Contextual Teaching And Learning, Prezi Desktop, Outcome